AT 2 Receptor Stimulation Increases Aortic Cyclic GMP in SHRSP by a Kinin-Dependent Mechanism - Peter Gohlke; Christiane Pees; Thomas Unger (1998)
In the present study we tested the hypothesis whether an angiotensin AT2 receptor-mediated stimulation of the bradykinin (BK)/nitric oxide (NO) system can account for the effects of AT1 receptor antagonism on aortic cGMP described previously in SHRSP. Adult SHRSP were treated for 4 hours with angiotensin II (ANG II) (30 ng/kg per min IV) or vehicle (0.9% NaCl I.V.). Animals were pretreated with vehicle, losartan (100 mg/kg P.O.), PD 123319 (30 mg/kg I.V.), losartan plus PD 123319, icatibant (500 microg/kg I.V.), N(G)-nitro-L-arginine methyl ester (L-NAME; 1 mg/kg I.V.), or minoxidil (3 mg/kg I.V.). Mean arterial blood pressure (MAP) was continuously monitored over the 4-hour experimental period, and plasma ANG II and aortic cGMP were measured by RIA at the end of the study. ANG II infusion over 4 hours raised MAP by about 20 mm Hg. Losartan alone or losartan plus ANG II as well as minoxidil plus ANG II markedly reduced blood pressure when compared to vehicle-treated or ANG II-treated animals, respectively. Plasma levels of ANG II were increased 2-fold by ANG II infusion alone or by ANG II in combination with icatibant, L-NAME, or minoxidil. The increase in plasma ANG II levels was even more pronounced after losartan treatment. Aortic cGMP content was significantly increased by ANG II, losartan, losartan plus ANG II, and minoxidil plus ANG II by 60%, 45%, 68%, and 52%, respectively (P<.05). The effects of ANG II and of losartan plus ANG II on aortic cGMP content were both blocked by cotreatment with the AT2 receptor antagonist PD 123319. Icatibant and L-NAME abolished the effects of ANG II on aortic cGMP. Our results demonstrate the following: (1) ANG II increases aortic cGMP by an AT2 receptor-mediated action because the effect could be prevented by an AT2 receptor antagonist; (2) the effect of ANG II was not secondary to blood pressure increase because it remained under reduction of MAP with minoxidil; (3) losartan increased aortic cGMP most likely by increasing plasma ANG II levels with a subsequent stimulation of AT2 receptors; and (4) the effects of AT2 receptor stimulation are mediated by BK and, subsequently, NO because they were abolished by B2 receptor blockade as well as by NO synthase inhibition.